The study on the exercise of discretionary power of the police under the peaceful assembly act 2012 / HazimMhd Nasruddin...[et al.] - Mhd Nasruddin, Hazim; Zainal Abidin, Adlina Atikah; Baharudin, Mohamed Hafiz; Ab Jalil, Ahmad Faris (Faculty of Law, 2014)
This paper is basically revolves around the area of the power of police and its discretionary power in policing a peaceful assembly according to the power granted by the Malaysian Peaceful Assembly Act (PAA) 2012. The centre of this project is concerning on section of 21 of the PAA which ambiguously worded the scope of police officers' power to disperse the assembly and immunity conferred to police officers for the force used in dispersing assembly. Further, the statute failed to provide any authority or procedure in scrutinising the decisions and the actions of police officers in exercising their power. Besides, this project paper compares the development and application of laws regarding policing peaceful assembly between Malaysian, United Kingdom and Australian legislation. The end result, we have proposed certain recommendations in respect the problems concerning the weaknesses of the PAA 2012 which have been focused in this paper.